Neuroplasticity in Early Onset Multiple Sclerosis - NASERMOGHADASI*, Abdorreza (Iranian Journal of Child Neurology, 2014)
How to Cite This Article: Naser Moghaddasi A. Neuroplasticity in Early Onset Multiple Sclerosis. Iran J Child Neurol. 2014Autumn;8(4): 80-81. Letter to Editor, Has not abstract. References Boiko A, Vorobeychik G, Paty D, Devonshire V, Sadovnick D; Neurologists. Early onset multiple sclerosis: a longitudinal study. Neurology 2002; 59(7):1006-10. Inaloo S, Haghbin S. Multiple Sclerosis in Children. Iran J Child Neurol 2013; 7(2):1-10. Ghezzi A. Therapeutic strategies in childhood multiple sclerosis. Ther Adv Neurol Disord 2010; 3(4): 217–228. Ferreira ML, Machado MI, Dantas MJ, Moreira AJ, Souza AM. Pediatric multiple sclerosis: analysis of clinical and epidemiological aspects according to National MS Society Consensus 2007. Arq Neuropsiquiatr 2008; 66(3B):665-70. Mundkur N. Neuroplasticity in children. Indian J Pediatr 2005; 72(10):855-7. A Naser-Moghadasi, M Owji. What can neuroplasticity tell us about the treatment of multiple sclerosis? Ir J Neurol 2013; 12(Suppl 1): 15. Anderson V, Spencer-Smith M, Wood A. Do children really recover better? Neurobehavioural plasticity after early brain insult. Brain 2011; 134(Pt 8):2197-221. Sale A, Berardi N, Maffei L. Environment and brain plasticity: towards an endogenous pharmacotherapy. Physiol Rev 2014; 94(1):189-234.